Contribution to study of eyed species of Sinella (Collembola: Entomobryidae), with a key to this group of species from China - Pan, Zhi-Xiang; Zhang, Feng; Shi, Shi-Di (Zootaxa, 2012)
Two new species, Sinella sunae n. sp. with 1+1 eyes and Sinella gei n. sp. with 5+5 eyes, are described in the presentpaper. Sinella umesaoi Yosii, 1940 is redescribed based on examination of a paratype and newly collected specimens from China. A key to the seventeen Chinese with eyes species of Sinella is provided.